Design Considerations for W-Shape Flexural Members Built-Up from Plates - Drake, Richard M.; Bankes, Michael E. (Engineering Journal, 2001)
It is common practice in some areas of the world to buildup or fabricate W-shapes from plate as alternates to rolled W-shapes. It is also possible that in order to meet project delivery schedules, a fabricator may request approval from the engineer-of-record to substitute a built-up W-shape for a temporarily unavailable rolled W-shape. In either case, it would be practicable if the engineer-of-record can select his Wshape members using the AISC Manual (AISC, 1994) and LRFD Specification (AISC, 1999) and companion design aids. This paper addresses design and/or fabrication issues for the practice and attempts to arrive at "rules" to allow safe and timely application.